Integration of Local Farmers' Knowledge for Sustainable Agriculture (Case Study of Horticultural Farmers in Waihatu Village) - Kakisina, Leunard Onisivorus (Future Science / FSH-PH Publications, 2023)
This research aims to explore farmer knowledge and learning practices with a focus on the role of informal knowledge and learning in strengthening agricultural sustainability and resilience. This research was conducted from May-June 2023 in the village of Waihatu, Kairatu District, West Seram Regency, Maluku Province, which is a center for horticultural crop production. This research uses a qualitative research design using case studies and in-depth interviews, observation, and document research. The results showed that the diversity of knowledge sources and forms of learning used by farmers and the special role of local farmer knowledge. That the knowledge potential of farmers is not utilized optimally and there are several ways in which various types of knowledge can be integrated by individual farmers by synthesizing knowledge from various sources, through farmer networks, both facilitated by formal agriculture and knowledge institutions, through collaboration between farmers and researchers as knowledge generators, and through multi-actor knowledge networks that bring together various fields. That dynamic context, complexity and local specificity of today's challenges facing agriculture and the many roles it is asked to fulfill requires more inclusive, flexible modes of knowledge generation, integration and sharing. All stakeholders and all types of knowledge need to be brought together on the same basis in the innovation process. To this end, policy frameworks and initiatives that promote interactive multi-actor approaches to development agriculture, can play a sizeable role.